Theaflavin Induces Apoptosis of A375 Human Melanoma Cells and Inhibits Tumor Growth in Xenograft Zebrafishes Through P53- and JNK-Related Mechanism - Zhang, Lei; Yan, Bo; Meng, Shijie; Zhou, Li; Xu, Yiqiao; Du, Wenxi; Shan, Letian (Frontiers in Pharmacology, 2020)
Theaflavin (TF) is a major active pigment and polyphenol of tea, possessing anti-cancer activities. However, little is known about its activity and mechanism on melanoma cells. To fill this gap, we conducted in vitro experiments (cell viability assay, morphology observation, DAPI staining, and flow cytometry) and in vivo experiment by using a xenograft model of larval zebrafishes. Real-time PCR (qPCR) and Western blot (WB) analyses were conducted to explore the mechanism of TF. The in vitro data showed that TF exerted significant anti-proliferative and pro-apoptotic effects on A375 cells in a concentration-dependent manner. In vivo, TF significantly inhibited A375 tumor growth in larval zebrafishes at 0.67 and 2.0 μg/ml (1.3 to 3.9 μM). qPCR and WB data showed that TF significantly activated the P53 pathway-related proteins (ATM, CHK1/2, P53, and CASP8/3) and the JNK pathway-related proteins (ASK1, JNK, and C-JUN) through phosphorylation and cleavage, followed by activation of pro-apoptotic molecules (PARP, BAX, BIM, PUMA, and P53). In sum, TF possessed cytotoxic pro-apoptotic and tumor-inhibitory effects on A375 cells through activations of P53 and JNK pathways. This is the first report on TF regarding its effects and mechanism on A375 cells, making it a promising candidate of natural products for clinical treatment of melanoma.